TOWARDS ECONOMICALLY INDEPENDENT VILLAGES: COMMUNITY EMPOWERMENT THROUGH THE PAHLAWAN EKONOMI NUSANTARA (PENA) PROGRAM IN BANYUMAS DISTRICT - Asyhabuddin; Alfi, Imam; Ageng (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
This research aims to find out how to empower the community through community business independence in the Nusantara Economic Heroes Program (PENA) in the Banyumas Regency. In the analysis process, this study uses the theory of ACTORS (Authority, Competence and Confidence, Trust, Opportunities, Responsibilities, and Support). The method used in this study is field research with data collection through observation, interviews, and documentation. The results of the study show that first, the PENA Program fosters the independence of its participants by encouraging the ownership of participants' authority in running their businesses. Second, PENA participants have high confidence that they can manage the business independently. Third, PENA participants have a high belief that the PENA program will bring changes to their social and economic conditions. Fourth, PENA participants feel that they are given a great opportunity to choose for themselves the business they will run. Fifth, PENA participants are fully responsible for the sustainability of the business they pioneer through the PENA program. And finally, PENA program participants get the support they need to start and continue their chosen business.